Progress Report to the International Monetary and Financial Committee on the Activities of the Independent Evaluation Office of the IMF. (Policy Papers; Policy Paper ;, 2016)
This report summarizes the outcome of the IEO's evaluation of The IMF and the Crises in Greece, Ireland, and Portugal, discussed by the Executive Board on July 19, 2016, and reports on recent follow-up and ongoing IEO work.